CFD modeling and experiment of heat transfer in a tubular photo-bioreactor for photo-fermentation bio-hydrogen production - Zhiping, Zhang; Quanguo, Zhang; Jianzhi, Yue; Lianhao, Li; Tian, Zhang; Zhengbai, Liu (International Journal of Agricultural and Biological Engineering, 2017)
Temperature is one of the most important parameters that need to be controlled in photo-fermentation bio-hydrogen production (PFHP) system. Since the high temperature and big temperature fluctuation have adverse impacts on bio-hydrogen yield, the system numerical simulation based on the operating conditions and environmental factors is desirable. This research focused on the investigation of heat transfer properties of the PFHP system. Enzymatic hydrolysate from agricultural residues was taken as substrate, and up-flow tubular photo-bioreactor was adopted for PFHP. Temperatures inside the photo-bioreactor were monitored. The experimental design and computational modeling for the determination of the heat transfer behavior in tubular photo-bioreactor was presented. Energy balance analysis was conducted to determine the energy efficiency, and optimize the operation parameters in order to obtain higher energy efficiency. The commercial software FLUENT was also adopted in order to predict the transient temperature distribution in the photo-bioreactor. The results showed that mathematical and computational modeling method has a clear potential for improving the performance of photo-bioreactor in the process of PFHP. Up-flow tubular bioreactor has tiny temperature fluctuant, and is suitable for PFHP.Keywords: photo-fermentation bio-hydrogen production (PFHP), up-flow tubular photo-bioreactor, heat transfer, temperature distribution, numerical simulationDOI: 10.3965/j.ijabe.20171001.2513Citation: Zhang Z P, Zhang Q G, Yue J Z, Li L H, Zhang T, Liu Z B. CFD modeling and experiment of heat transfer in a tubular photo-bioreactor for photo-fermentation bio-hydrogen production. Int J Agric & Biol Eng, 2017; 10(1): 209–217.